The Impact of Various Factors on the Effectiveness of Internal Audit in the Public Sector: The Case of Bosnia and Herzegovina - Benina Veledar; Amra Gadžo; Nejra Bajrić (Journal of Forensic Accounting Profession, 2024)
The paper focuses on analyzing key factors influencing the effectiveness of internal audit in the public sector of Bosnia and Herzegovina (BiH). Through multiple regression analysis (Ordinary Least Squares-OLS), the impact of five independent variables (competence of internal auditors, size of internal audit department, relationship between internal and external auditors, management support for internal audit, and independence of internal auditors), two control variables (organization's sector and total number of employees in the organization), on the dependent variable (effectiveness of internal audit) was measured. Research results indicate that a significant portion (.2 = 45.00%, Adj .2 = 40.90%) of the variability in the effectiveness of internal audit can be explained by the variability of the five independent variables in the model. The largest positive impact on the effectiveness of internal audit is attributed to the size of the internal audit department and the independence of internal auditors. Conversely, management support for internal audit had the least impact, which contradicts our predictions and the results of previous research. The limited impact of management support on the effectiveness of internal audit in the public sector of BiH may stem from a lack of understanding regarding the role and importance of internal audit, as well as from perceiving it as merely a formal legal requirement without substantial value.
Keywords: M40; 650; public sector; internal audit; effectiveness of internal audit